Bioupravlenie v meditsine i fizicheskoi kul'ture - Kuchkin, S. N. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The lecture is devoted to the problem of the biological control in medicine and physical culture. The system of biological control is considered in connection of the biological feedback. The practice of the biological control is analysed on the examples of the respiration function's control, the operation teaching, the physical culture and sport, the homeostasis'es control. The ways to realize the method of biological control method, basing on the biological feedback are discribed.